Online and face-to-face role-play simulations in promoting social work students’ argumentative problem solving (Journal of Comparative Social Work, 2013)
This paper reports on a teaching experiment in which social work students (n=38) practiced problem solving through argumentative tasks. A teaching experiment was carried out at a Mikkeli University of Applied Sciences in Finland in connection with a course concerning preventative work against alcohol- and drug abuse. This quasi- experimental study investigated whether role-play simulation conducted either online (15 students) or face-to-face (14 students) improved students’ problem solving on social issues. As a pre-test, the students wrote an essay after having watched a dramatization of problematic cases on elderly people’s use of alcohol. The students also attended lectures (30 x 45 min) on the effect of substance abuse and preventive work, and after the role-play simulation they wrote another essay (post-test). Nine controls wrote an essay without participating in the role-play simulation. Lastly, the students filled out feedback questionnaires.